Long‐term anti‐endotoxin/E. coli efficacy in mice transfected with AAV2/1‐muBPI25‐muFcγ1. Issue 10 (8th August 2016) - Lv, Zhe; Fan, Yiqiang; Xu, Qing; Kong, Qingli; Li, Chen; Liu, Zhenlong; Wang, Wei; An, Yunqing
Abstract : Bactericidal/permeability increasing (BPI) is an antibiotic protein which kills Gram‐negative bacteria and neutralizes endotoxin. We have previously developed a recombinant adeno‐associated virus which contains human BPI amino acid residues 1–199 and Fc fragment of human IgG1 gene (AAV‐hBPI‐Fc) and shown that the recombinant virus can protect mice from lethal endotoxemia. However, whether AAV‐hBPI‐Fc can be used in vivo for the long term remains unclear. To address this, we established an adeno‐associated virus‐containing mouse BPI and Fc fragment genes (muBPI‐Fc) and compared antigenicity of these recombinant proteins in murine models. Immunohistochemistry showed the expression of both fusion proteins at injected sites. ELISA and Western blotting showed that the muBPI‐Fc protein was detected in serum up to 8 weeks after injection, without generation of autoantibodies against muBPI‐Fc. In contrast, expressed hBPI‐Fc protein was only detected on the 2nd week, whereas the autoantibody against hBPI‐Fc protein occurred in serum from the 4th week to the end of study. muBPI‐Fc also reduced production of proinflammatory cytokines and protected mice from endotoxemia and bacteremia. Our data showed that AAV‐muBPI‐Fc has potential long‐term efficacy as an anti‐endotoxin and has anti‐bacterial activity in mice, suggesting the potential clinical application of AAV‐hBPI‐Fc, such as in endotoxin shock.